Developmental language disorder – a comprehensive study of more than 46, 000 individuals. (May 2023) - Nudel, Ron; Christensen, Rikke Vang; Kalnak, Nelli; Schwinn, Michael; Banasik, Karina; Dinh, Khoa Manh; Erikstrup, Christian; Pedersen, Ole Birger; Burgdorf, Kristoffer Sølvsten; Ullum, Henrik; Ostrowski, Sisse Rye; Hansen, Thomas Folkmann; et al.
Highlights: DLD is a common, but relatively under-investigated, neurodevelopmental disorder. The study investigated language disorders in a nationwide cohort of adults, the Danish blood donor study (DBDS) cohort. Results showed that DLD is extremely underdiagnosed in the hospital registers. DLD has a negative effect on mental and physical health outcomes in adults, and adults with DLD have an increased risk of reading and learning difficulties. Genetic analysis identified a genome-wide significant locus for DLD. There is a need for raising awareness of DLD in the general public and specifically among healthcare professionals. Abstract: Developmental language disorder (DLD) is characterized by enduring low language abilities with a significant functional impact, in the absence of biomedical conditions in which language impairment is part of a complex of impairments. There is a lack of awareness of DLD even among healthcare professionals. Here we estimated the prevalence of DLD and its links to reading and learning difficulties and physical and mental health in the Danish Blood Donor Study ( N  = 46, 547), where DLD-related information is based on questionnaires (self-report). We compared the questionnaire-derived DLD status with the relevant language-related diagnoses from hospital registers. We also investigated the genetic architecture of DLD in a subset of the cohort ( N  = 18, 380). DLD was significantly associated with reading and learning difficulties and poorer mental and physical health. DLD prevalence was 3.36%–3.70% based on questionnaires, compared with 0.04% in hospital registers. Our genetic analyses identified one genome-wide significant locus, but not a significant heritability estimate. Our study shows that DLD has health-related implications that may last into adulthood, and that DLD may be undiagnosed in general healthcare. Furthermore, DLD is likely more genetically heterogeneous than narrower developmental language phenotypes. Our results emphasize the need to raise awareness of DLD and consider criteria for molecular studies of DLD to reduce case heterogeneity.